Contrasting P-T-t paths for Neoproterozoic metamorphism in MacRobertson and Kemp Lands, east Antarctica - Jacqueline Halpin; Clarke, GL; White, RW; Kelsey, DE (2007)
Mineral equilibria modelling and electron microprobe chemical dating of monazite in granulite facies metapelitic assemblages from the MacRobertson Land coastline, Rayner Complex, east Antarctica, are consistent with an 'anticlockwise' Neoproterozoic P-T-t path. Metamorphism occurred at c. 990-970 Ma, achieving peak conditions of 850 °C and 5.6-6.2 kbar at Cape Bruce, and 900 °C and 5.4-6.2 kbar at the Forbes Glacier ∼50 km to the east. These peak metamorphic conditions preceded the emplacement of regionally extensive syntectonic charnockite. High temperature conditions are likely to have been sustained for 80 Myr by lithospheric thinning and repeated pluton emplacement; advection was accompanied by crustal thickening to maximum pressures of 6-7 kbar, followed by near-isobaric cooling. This P-T-t path is distinct from that of rocks in adjacent Kemp Land, ∼50 km to the west, where a 'clockwise' P-T-t path from higher- P conditions at c. 940 Ma may reflect the response of a cratonic margin displaced from the main magma flux. In this scenario, crustal shortening was initially accommodated in younger, fertile crust (MacRobertson Land) involving metasediments and felsic plutons with the transfer of strain to adjacent older crust (Kemp Land) subsequent to charnockite emplacement. © 2007 Blackwell Publishing Ltd.